Managerial Factors Influencing the Empowerment of Student Teachers: Developing and Validating a Model Based on a Mixed-Methods Approach (Qualitative–Qualitative–Quantitative) - Nazarizadeh, Marzieh; Khorasani, Abasalt; Shams, Gholamreza; Ebrahimi, Ayoub (Assessment and Practice in Educational Sciences, 2025)
Achieving school effectiveness requires the empowerment of teachers within schools. Teacher empowerment is a critical factor in improving the quality of education, benefiting learners, teachers, schools, and the broader educational landscape. Therefore, the present study aimed to design and validate the managerial factors that influence the empowerment of student teachers. The research employed a sequential exploratory strategy with a mixed-methods approach (qualitative meta-synthesis – qualitative interviews – quantitative validation). Participants in the meta-synthesis phase included all Persian and English books, research studies, and scholarly works conducted in the field of empowerment between 2010 and 2024, resulting in the selection of 61 studies. In the interview phase, participants consisted of experts, professors, and specialists from teacher education universities who were engaged in the development and empowerment of students, student teachers, and related areas of educational development and human capital empowerment. Using purposive and snowball sampling, 17 experts were selected. In the quantitative phase, the statistical population consisted of student teachers enrolled during the 2024–2025 academic year, among whom 90 individuals were selected as the sample. Data collection instruments included a checklist for the qualitative meta-synthesis phase, semi-structured interviews with experts, and a researcher-made questionnaire for the quantitative phase. The validity and reliability of the questionnaires were confirmed by field specialists. For data analysis, thematic analysis was used in the qualitative phase, while descriptive and inferential statistics were applied in the quantitative phase using SPSS and SmartPLS 3.8 software. Overall, the findings indicated that managerial factors influencing the empowerment of student teachers can be conceptualized in three main domains: managerial styles (five components), management tasks (seven components), and managerial competencies (six components). The results of structural equation modeling confirmed the validity of the proposed model. Based on these findings, it appears that the process of enhancing teachers’ capabilities and performance, as well as formulating effective educational policies and practices, strongly depends on professional development activities.